Travel & leisure: best afternoon tea places in Penang / Noraziah Mohd Amin - Mohd Amin, Noraziah (Academy of Language Studies, 2023)
Is tea your cup of tea? If the answer is "yes", you will probably enjoy sitting down for afternoon tea. As its name suggests, afternoon tea is usually served between 3.00 pm to 6.00 pm. Restaurants serving pastries, coffee and tea might offer afternoon tea sets with choices of sweet and savory pastries. Afternoon tea is basically a meal after a meal to satisfy "that sinking feeling" and it is quite different to another in between meals called, "high tea". According to "Top 12 Best High Tea in Penang 2022" (2022), the mouth watering pastries such as scones, sandwiches, and cakes that are served for day tea in the middle of the day is called "afternoon tea". High tea, in contrast, is served in the early evening and has much heartier fare such as meat, poultry, fish, and egg delicacies apart from bread and sweets treats. If you have read the book, Alice's Adventures in Wonderland, an 1865 English novel by Lewis Carrol, you have probably read a chapter on afternoon tea under the title, "A Mad Tea-Party". However, unlike the tea party in the novel, the standard afternoon tea is usually served without wine but a variety of teas as a replacement. Some of the basic types of tea usually prepared for afternoon tea are English Breakfast which is a great black tea, sipped with milk or lemon; Irish Breakfast.